2019
DOI: 10.1101/645226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insulin-like growth factor 1 is related to the expression of plumage traits in a passerine species

Abstract: Avian plumage colors and ornaments are ideal models to study the endocrine mechanisms linking sexually selected traits and individual parameters of quality and condition. The insulinlike growth factor 1 (IGF-1), an evolutionarily highly conserved peptide hormone, represents a link between body condition and the individual capacity to grow elaborated ornamental features, due to its regulatory role in cell proliferation and differentiation and its high sensitivity to the nutritional state of individuals. We inve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Plasma IGF‐1 levels were measured by a competitive ELISA at the University of Debrecen described in detail in Mahr et al (2020). Briefly, 96‐well microplates were coated at 4°C overnight with 100 µl of an antibody raised against IGF‐1 in rabbits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma IGF‐1 levels were measured by a competitive ELISA at the University of Debrecen described in detail in Mahr et al (2020). Briefly, 96‐well microplates were coated at 4°C overnight with 100 µl of an antibody raised against IGF‐1 in rabbits.…”
Section: Methodsmentioning
confidence: 99%
“…In free-living passerines, there was one study that detected an association between plasma IGF-1 levels and egg weight, and the direction of the association depended on the species' body weight (Lodjak et al 2018). Furthermore, it was reported that IGF-1 could play a role in the development of sexually selected ornaments in a sexually dichromatic passerine species, the bearded reedling (Mahr et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin‐like growth factor (IGF) signalling pathway in rhinoceros beetles ( Trypoxylus dichotomus ) is one such example of a mechanism in which horn tissues have heightened sensitivity to the physiological correlates of foraging success, producing large male morphs when a certain threshold for the physiological correlate, relating to juvenile nutrition, is exceeded (Emlen et al, 2012). Similar mechanisms have been implicated in a range of sexually selected characters in both holometabolous and hemimetabolous invertebrates (Nijhout & McKenna, 2018) and may be applicable to some vertebrates as well (Mahr et al, 2020). By their nature, we would expect that the heritable scaling relationships of ancestors must impact the allometries of descendants.…”
Section: Introductionmentioning
confidence: 78%
“…Plasma IGF-1 levels were measured by a competitive ELISA at the University of Debrecen described previously in Mahr et al (2020). Briefly, 96-well microplates were coated at 4°C overnight with 100 µl of an antibody raised against IGF-1 in rabbits.…”
Section: Methodsmentioning
confidence: 99%
“…There is only a handful of studies examining the role of IGF-1 in regulating life-history traits of wild animal species, and even fewer testing the effects of an experimental increase of systemic IGF-1 on their physiology and behaviour (Dantzer & Swanson 2012; Lodjak & Verhulst 2020; Montoya et al 2022). In the bearded reedling, IGF-1 has been studied in various contexts and is associated with regulating the stress response (Tóth, Ouyang & Lendvai 2018), ornament expression (Mahr et al 2020) and feather moult (Lendvai et al 2021). Lendvai et al (2021) has shown that one single subcutaneous injection of PLGA microparticles loaded with IGF-1 resulted in a significant elevation of IGF-1 on day 1 post-injection and was sufficient to alter moult patterns and feather quality.…”
Section: Introductionmentioning
confidence: 99%